Building Consumer Trust Through Information System Integration in E-Commerce - Sitti Hasbiah; Ilma Wulansari Hasdiansa (Lafadz Jaya Publisher, 2025)
This study examines how well integrated information systems can enhance user trust by addressing key aspects such as data security, ease of access, and platform reliability. Through a literature review and analysis of online data sources, the study reveals that transparent and reliable information systems foster user loyalty and strengthen the relationship between consumers and e-commerce service providers. Furthermore, the study emphasizes that trust is a critical determinant in the user decision making process, especially in a digital environment where direct interaction is minimal. Integrated systems that prioritize user experience and consistent service delivery significantly reduce uncertainty and perceived risk among users. The findings also show that when users perceive a platform as secure and responsive, their engagement levels increase, resulting in higher retention rates and positive word of mouth. This underscores the importance of continuous system evaluation, inclusion of user feedback, and proactive risk management as strategic components of information system development. In conclusion, investing in robust, user-centric information systems not only improves operational efficiency but also builds sustainable competitive advantage through fostering user trust. This study contributes to the growing discourse on digital trust and offers practical insights for e-commerce providers looking to strengthen their customer relationships through technology integration.